2024
DOI: 10.3390/molecules29020434
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Preventive Effects of Thymoquinone against Breast Cancer: Role of DNMT1

Mohammed Kaleem,
Asaad Kayali,
Ryan A. Sheikh
et al.

Abstract: Breast cancer (BC) is one of the most common cancers in women and is a major cause of female cancer-related deaths. BC is a multifactorial disease caused by the dysregulation of many genes, raising the need to find novel drugs that function by targeting several signaling pathways. The antitumoral drug thymoquinone (TQ), found in black seed oil, has multitargeting properties against several signaling pathways. This study evaluated the inhibitory effects of TQ on the MCF7 and T47D human breast cancer cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…TQ is the biologically active constituent found in black cumin ( Nigella sativa ) seeds. 162 Several studies have demonstrated the effectiveness of TQ in treating neoplasms, including skin, ovarian, breast, colon, prostate, liver, and cervical malignancies. 162 164 To sum up, this study’s results showed that TQ blocked the β-catenin signaling pathway, which in turn prevented melanogenesis in B16F10 murine melanoma cells, as well as zebrafish melanogenesis.…”
Section: Therapeutic Strategies For the Treatment Of Skin Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…TQ is the biologically active constituent found in black cumin ( Nigella sativa ) seeds. 162 Several studies have demonstrated the effectiveness of TQ in treating neoplasms, including skin, ovarian, breast, colon, prostate, liver, and cervical malignancies. 162 164 To sum up, this study’s results showed that TQ blocked the β-catenin signaling pathway, which in turn prevented melanogenesis in B16F10 murine melanoma cells, as well as zebrafish melanogenesis.…”
Section: Therapeutic Strategies For the Treatment Of Skin Cancermentioning
confidence: 99%
“… 162 Several studies have demonstrated the effectiveness of TQ in treating neoplasms, including skin, ovarian, breast, colon, prostate, liver, and cervical malignancies. 162 164 To sum up, this study’s results showed that TQ blocked the β-catenin signaling pathway, which in turn prevented melanogenesis in B16F10 murine melanoma cells, as well as zebrafish melanogenesis. TQ did not appear to be harmful to normal melanocytes, but it was toxic to both of the melanoma cell lines that were investigated.…”
Section: Therapeutic Strategies For the Treatment Of Skin Cancermentioning
confidence: 99%
“…[1][2][3] It is caused by an imbalance between the expression of oncogenes and proto-oncogenes, which is caused by genetic and epigenetic abnormalities. 4,5 Globally, the number of cancer diagnoses has climbed to 19.3 million, and each year, 10 million deaths related to cancer are reported. The most common type of cancer among women is breast cancer (BC), globally.…”
Section: Introductionmentioning
confidence: 99%